2022
DOI: 10.1186/s12860-022-00428-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the media conditioned by various macrophage subtypes derived from THP-1 cells on tunneling nanotube formation in pancreatic cancer cells

Abstract: Background Tunneling nanotubes (TNTs) are special membrane structures for intercellular communications. Vital cargoes (such as mitochondria) could be delivered from healthy cells to rescue damaged ones through TNTs. The TNTs could be utilized for the purpose of systematic delivery of therapeutic agents between cells. However, there are insufficient studies on the controlled enhancement of TNT formations. The purpose of this study is to understand how macrophages influence the TNT formation in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Due to its involvement in neurological diseases, mitochondrial transport is one of the most widely studied processes in NT research. Based on these investigations, the direction of mitochondria transport may vary, and depending on the cell type, it can be either unidirectional, where mitochondria are transported from healthy cells to damaged cells via NTs supporting cell survival (e.g., from pericytes to astrocytes, in PC12 and normal porcine urothelial /NPU/ cells, or from bone marrow stromal cells to acute myeloid leukaemic cells to improve resistance against chemotherapy) [24,45,70,71] or bidirectional (e.g., between human umbilical vein endothelial cells /HUVECs/ and mesenchymal stem cells /MSCs/, or between Jurkat cells and MSCs [72][73][74][75][76]. The main molecular components of mitochondrial delivery have already been identified; however, since these results are often contradictory, the exact mechanism of their transfer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its involvement in neurological diseases, mitochondrial transport is one of the most widely studied processes in NT research. Based on these investigations, the direction of mitochondria transport may vary, and depending on the cell type, it can be either unidirectional, where mitochondria are transported from healthy cells to damaged cells via NTs supporting cell survival (e.g., from pericytes to astrocytes, in PC12 and normal porcine urothelial /NPU/ cells, or from bone marrow stromal cells to acute myeloid leukaemic cells to improve resistance against chemotherapy) [24,45,70,71] or bidirectional (e.g., between human umbilical vein endothelial cells /HUVECs/ and mesenchymal stem cells /MSCs/, or between Jurkat cells and MSCs [72][73][74][75][76]. The main molecular components of mitochondrial delivery have already been identified; however, since these results are often contradictory, the exact mechanism of their transfer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that the movement of mitochondria can be facilitated by various motor proteins that rely on the cytoskeleton. Certain studies linked the transport of mitochondria to the microtubule-based kinesin motor protein [24,44,72]. Others propose that the mitochondrial transport in NTs may occur independently of microtubules, suggesting an alternative mechanism [46,77].…”
Section: Discussionmentioning
confidence: 99%
“…from pericytes to astrocytes, in PC12 and normal porcine urothelial /NPU/ cells, or from bone marrow stromal cells to acute myeloid leukemic cells to improve resistance against chemotherapy) [24,45,70,71] or bidirectional (e.g. between human umbilical vein endothelial cells /HUVEC/ and mesenchymal stem cells /MSC/, or between Jurkat and MSCs [72][73][74][75][76]. The main molecular components of mitochondria delivery have already been identified, however, since these results are often contradictory, the exact mechanism of their transfer is still unclear, in addition, regulatory proteins involved in the mitochondria transport of B cell TNTs were not investigated at Several studies have confirmed that the movement of mitochondria can be facilitated by various motor proteins that rely on the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The main molecular components of mitochondria delivery have already been identified, however, since these results are often contradictory, the exact mechanism of their transfer is still unclear, in addition, regulatory proteins involved in the mitochondria transport of B cell TNTs were not investigated at Several studies have confirmed that the movement of mitochondria can be facilitated by various motor proteins that rely on the cytoskeleton. Certain studies linked the transport of mitochondria to the microtubule-based kinesin motor protein [24,44,72]. Others propose that the mitochondria transport in NTs may occur independently of microtubules, suggesting an alternative mechanism [46,77].…”
Section: Discussionmentioning
confidence: 99%
“…Tunneling nanotubes appear to be important factors in the interactions between tumor cells and macrophages, which may lead to tumor progression and the formation of metastases [ 203 ]. Recently, Lee et al [ 204 ] showed that media conditioned by M0 and M1, but not M2, macrophages strongly stimulate the formation of TNTs in human pancreatic cancer cells (PANC-1), which correlates with increased PANC-1 mobility and epithelial-mesenchymal transition; transport of mitochondria and lysosomes via TNTs also occurs. TNTs may play a primary role in the earliest phases of both physiological and tumor angiogenesis in the brain [ 205 ].…”
Section: Membrane Protrusions: Cytonemes Tunneling Nanotubes and Inte...mentioning
confidence: 99%